THE EFFECT OF SWEETENER TO THE FORMULATION OF LOZENGES TABLET FROM CITRUS FRUIT PEELS PONTIANAK’S ESSENTIAL OILS - Ella Sriasih; Wintari Taurina; Rafika Sari (Majalah Farmaseutik, 2016)
Pontianak orange (Citrus nobilis Lour. var. microcarpa) has good benefit for health. Adding value of peel waste, it can be the waste of Pontianak citrus it can be formulated into lozenges contains essential oils. The lozenges were made by direct compress method with variation of manitol-sukrose ratio as sweetening agent. Formula 1 uses sucrose as sweetener, formula 2 employs combination of manitol-sukrose (1:1). Meanwhile, formula 3 uses manitol as sweetening agent. Based on the research, it showed that variations of the sweetener affect the physical properties of lozenges. Friability test of the tablet performed significant difference between formula 1 and formula 2 which formula 1 is better than formula 2 in friability. Taste test and preference of the respondent showed formula 1 as the most preferred with score of 124 in flavor aspect and texture with score of 113.